Solid-State Metathetic Synthesis and Photoluminescence of BaMoO4 Assisted by Cyclic Microwave Irradiation - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
A solid-state metathetic route assisted by microwave irradiation was used to synthesize BaMoO4 particles under environmentally friendly conditions. Well crystallized BaMoO4 particles were formed at 400-600 ºC for 3 h, showing fine and homogeneous morphologies with particle sizes of 1-2 μm. The synthesized BaMoO4 particles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The optical properties were investigated by photoluminescence emission and Raman spectroscopy.